Influence of controlled release fertilizer on the production of Enterolobium schomburgkii (Benth.) - Thiago José Lavareda Lima; Cleverson Agueiro de Carvalho; Márcio Chaves da Silva; Bárbara Barbosa Mota; Márcia Chaves da Silva; Roger Ventura Oliveira; Regina Lúcia Felix Ferreira (Scientific Electronic Archives, 2023)
The forest species Enterolobium schomburgkii Benth. It is a fast-growing legume with potential for use in plantations and recovery of degraded areas. Thus, knowing the nutritional demands of this species in the seedling formation stage is essential for the success of its implantation in the field. Therefore, the objective of this work is to evaluate the development of seedlings of E. schomburgkii Benth. with the application of controlled release fertilizer doses. The experiment was carried out at the seedling production nursery of the Technology Foundation of the State of Acre, from May to September 2022. The experimental design used was completely randomized, with 8 treatments and 10 replications. The treatments were at different doses of controlled release fertilizer, as follows: T1 = 0 g/L-1; T2 = 2 g/L-1; T3 = 4 g/L-1; T4 = 6 g/L-1; T5 = 8 g/L-1; T6 = 10 g/L-1; T7 = 12 g/L-1 and T8 = 14 g/L-1. The morphological parameters evaluated were the stem diameter (DC) and height (H) of the seedlings, carried out 120 days after sowing. The use of a dose of 6 g/L-1 of controlled release fertilizer indicates optimization of the production of Enterolobium schomburgkii seedlings.